Correlation between Pre Pregnancy BMI and 6 weeks’ Weight Retention - Banan Natiq Turkey; ELAF YOUSIF RASHID; qais ismaeel kadhem (YCAB Publisher, 2026)
Background: As there is increasing interest about the weight and ideal weight before getting pregnant and it effect on maternal and fetal outcome, with importance of long term effect of weight retention on maternal health. Objective: we are aiming by this study to focus on the relation of the pre pregnancy BMI with 6-weeks post-partum weight retention. Method: A retrospective study was conducted during a period of 3 months (1st of March- 1st of June) at 2024. The data collected from obstetric record of Babil Teaching Hospital for Maternity and Children /Babil Iraq in IRAQ, where data of 100 women who give birth to singleton baby was taken including age, educational level, exercise, dietary restriction, pre-pregnancy BMI, weight gain in each trimester, fetus numbers, mode of delivery, weight 6 weeks after delivery, any medical disease before or during pregnancy. Result: We found that 57% of women ranging from 26-35year ,32% ranging from 18-25year and 11% ranging from 36-45 years, that with normal weight 28%, overweight 40% and obese 32%, also 6weeks post-partum weight 68% of women retained less than 5 kg and 32 % of women retained more than 5 kg, and There was significant association between participant’s pre-pregnancy BMI with weight gain during the pregnancy and 6 weeks’ postpartum weight retention as p value was 0.024 and 0.001 respectively. Conclusion: Pre-pregnancy BMI and gestational weight gain has positive correlation with 6-weeks post-partum weight retention Keywords: Correlation; Pre pregnancy; BMI; weight retention